The Utilization of Fuzzy Logic Controllers in Steering Control Systems for Electric Ambulance Golf Carts - Chotikunnan, Rawiphon; Chotikunnan, Phichitphon; Imura, Pariwat; Pititheeraphab, Yutthana; Thongpance, Nuntachai (International Journal of Robotics and Control Systems, 2024)
This study investigates methods to improve steering control for electric ambulance golf carts by conducting a comparative analysis of fuzzy logic controllers. The research assesses four control systems, PD controller, fuzzy PD controller, fuzzy PD+I controller, and PBC and PD+I type fuzzy logic controller, to determine their effectiveness in enhancing steering control. Simulink simulations are employed to evaluate the performance of these controllers under various conditions. Results indicate that the PBC and PD+I type fuzzy logic controller demonstrates superior performance, showing significant reductions in both rise time and settling time with minimal overshoot compared to other controllers. The findings underscore the potential of fuzzy logic controllers in enhancing steering control for electric vehicles. Future research should explore alternative control strategies and assess controller robustness under diverse operating conditions.